1998
DOI: 10.1183/09031936.98.12061271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-dose acetazolamide on the ventilatory CO2 response during hypoxia in the anaesthetized cat

Abstract: The carbonic anhydrase inhibitor acetazolamide stimulates ventilation, resulting in an improvement in arterial oxygen tension (Pa,O 2 ) in patients with chronic obstructive pulmonary disease (COPD) or central sleep apnoea syndrome and in those suffering from acute mountain sickness [1][2][3][4][5][6][7][8][9][10]. The ventilatory effect with the drug is believed to be mediated by a metabolic acidosis, induced by inhibition of renal carbonic anhydrase [11][12][13][14]. However, other local effects of acetazolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
18
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
7
18
1
Order By: Relevance
“…Our findings are in agreement with previous rebreathing experiments performed on rats (Adams & Johnson, 1990), but not with steady-state experiments performed on humans (Swenson & Hughes, 1993) or cats (Wagenaar et al 1998). They are also in agreement with findings reported from chronic ACZ studies using the rebreathing method (Tojima et al 1986;Bashir et al 1990).…”
Section: Central Chemoreflexsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are in agreement with previous rebreathing experiments performed on rats (Adams & Johnson, 1990), but not with steady-state experiments performed on humans (Swenson & Hughes, 1993) or cats (Wagenaar et al 1998). They are also in agreement with findings reported from chronic ACZ studies using the rebreathing method (Tojima et al 1986;Bashir et al 1990).…”
Section: Central Chemoreflexsupporting
confidence: 93%
“…Other studies have also shown that inhibition of CA blunts or inhibits the peripheral chemoreflex drive to ventilation. This was demonstrated in cats (Wagenaar et al 1998) and humans (Swenson & Hughes, 1993) whereby the ventilatory response to hypoxia was suppressed following ACZ. However, the influence of CA inhibition on the central chemoreflex is less conclusive.…”
mentioning
confidence: 84%
See 3 more Smart Citations